Regulation of metallothionein gene expression in dental pulp cells - Yukihiko Tamura; Pornpoj Fuangtharnthip (Elsevier, 2021)
Aim or Purpose: Metallothionein (MT) is a cysteine-rich metal-binding protein. Zinc (Zn) is one of the inducers for expression of MT in many organs. It is widely believed that MT functions in the detoxification of heavy metals such as cadmium (Cd). In addition, it has been suggested MT plays an antioxidative role in the inflammation since MT has many sulfhydryl groups. In this study, we investigated the pharmacological significance of MT induced by Interleukin-6 (IL-6), one of the inflammatory cytokines in dental pulp cells. Materials and Methods: IL-6 was added to dental pulp cells, which were cultured by the usual method, and the changes in gene expression of MT were analyzed 1, 6, 24 hours after IL-6 or Zn treatment by using real-time RT-PCR. In addition, Cd was added to the culture medium after Zn treatment, and cytotoxicity was observed using LDH assay, and cell viability assay. The means of each treatment were compared using Student's t-test. Results: Cd toxicity has been reduced by MT induction by Zn pretreatment. The gene expression of MT increased within 6 hours after Zn treatment. The IL-6 treatment increased MT gene expression after 6 hours. It showed that there is a difference in the reactivity of MT gene expression by the type of stimulation to pulp cells. Conclusions: Since IL-6 is known to be involved in the onset and progress of pulpitis, the MT of dental pulp could work as a multifunctional protein induced during inflammation as well as a biological defense reaction to heavy metals.